Maternal Socio-Demographic Factors and Mother-to-Child Transmission of HIV in the North Region of Cameroon - Celine Nguefeu Nkenfou; Marie-Nicole Ngoufack; Georges Nguefack-Tsague; Barbara Atogho; Constantin Tchakounte; Brian Bongwong; Carine Nguefeu-Tchinda; Elise Elong; Laeticia-Grace Yatchou; Joel Kameni; Aline Tiga; Wilfred F Mbacham; et al. (Global Health and Education Projects, Inc., 2023)
Background and Objective: Socio-demographic factors are important risk factors for HIV infection. Maternal socio-demographic factors associated with HIV transmission from mother to child are not well elucidated to our knowledge. This study aimed to assess the maternal socio-demographic factors associated with HIV vertical transmission. Methods: A matched case-control study was conducted among children under 15 years of age born to HIV-infected mothers; using a structured questionnaire. The study was conducted in four health facilities in the North Region of Cameroon from July 2015 to October 2016. HIV- infected children were the cases, and HIV-uninfected children were the controls. One case was matched to nearly 4 controls according to age and sex. A total of 113 HIV-infected mothers of children under 15 years of age were purposively enrolled in the study. A questionnaire was administered to mothers and socio-demographic characteristics were collected. Blood samples were collected from the mother and her child for the determination or confirmation of HIV status. Univariate and multiple logistic regressions were used to assess associations between socio-demographic variables and HIV transmission from mother to child. Results: A total of 113 HIV-infected mothers and 113 children under 15 years of age were enrolled in this study. The majority of the mothers were between the age ranges of 25 years to 34 years. Of the 113 HIV-infected mothers, 69 (61%) were Muslims, 33 (32.1%) were not educated, 88 (77.8%) were unemployed, 80 (70.9%) were married, out of which 49 (61.6%) were engaged in a monogamous union. Of the 113 children (49.6%) were female, 25 (22.1%) were HIV-infected and 88 (77.9%) were HIV-exposed uninfected. At the univariate level, mothers who achieved a primary level of education were less likely to transmit HIV to infants compared to uneducated mothers [OR=0.28; CI (0.08-0.95); p=0.04]; and widows had a higher likelihood of HIV transmission to infants compared to married mothers [OR=4.65; CI (1.26-17.20); p=0.02]. Using multiple logistic regression, the maternal primary education level [aOR=0.32; CI (0.08-0.90); p=0.03] and widowerhood [aOR=7.05; CI (1.49-33.24); p=0.01] remained highly associated with the likelihood of HIV transmission to infants. Conclusion and Global Health Implications: Uneducated mothers and widows had a higher likelihood of mother-to-child transmission of HIV. Our findings should prompt reinforcement of prevention strategies targeting uneducated women and widows.   Copyright © 2022 Nkenfou et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0.